ANALISIS POLA ASUH WORKING MOM DALAM MENANAMKAN NILAI KEAGAMAAN DAN MOTIVASI BELAJAR ANAK - Ana Aniati; Humaida, Aniq; Nasrodin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and analyze in depth the parenting patterns employed by working mothers in instilling religious values and enhancing children's learning motivation. The research employed a qualitative approach using a case study design. The study was conducted from February to April 2026 in Parijatah Wetan Village, Srono District, Banyuwangi Regency, Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing/verification.The findings reveal that working mothers in Parijatah Wetan Village, Srono District, Banyuwangi Regency implement various parenting styles, with a tendency toward authoritarian parenting characterized by the establishment of clear rules and boundaries for children. In fostering religious values and learning motivation, these mothers primarily emphasize role modeling through the habituation of religious practices, such as performing the five daily prayers, observing Ramadan fasting, and reciting the Qur’an from the elementary school level. This approach has proven to be relatively effective in shaping children's religious behavior, although continuous supervision and periodic reminders remain necessary to ensure consistency